Tajemnice i poszukiwanie bezpieczeństwa. O sposobach utraty tajemnic inadziejach na ich odzyskanie. Część II - Szulakiewicz, Marek (Humaniora. Czasopismo Internetowe, 2024)
Mysteries have appeared in many areas of past culture as one of the prerequisites for asking about the world. However, the old forms of their appearance and the philosophers’ (Heidegger’s) dreams of the necessity of returning to them belong to the past. The article attempts to answer the question of the meaning of mystery in our culture, philosophy and religion. It characterises the social and metaphysical dimensions of the secret and contrasts secret and mystery. In metaphysical terms, the secret refers to the way in which the world and man exist, and not to a lack of knowledge. In it (and through it) the world appears as not complete, not fulfilled, not finished and always unfinished, but open to new possibilities. The text also shows and discusses the processes of demystification and their consequences for man and culture. The last section of the article shows areas in which the hope for a restoration of culture has remained. These are religion and science. In its essential aspect, religion is naturally interwoven with mystery. Modern science also takes a “step back” in the face of a soulless and objectified reality. It maximises the role of the cognitive subject and minimises the objectification of the world.